Bioethanol production from wheat straw by phosphoric acid plus hydrogen peroxide (PHP) pretreatment via simultaneous saccharification and fermentation (SSF) at high solid loadings. (November 2018) - Qiu, Jingwen; Tian, Dong; Shen, Fei; Hu, Jinguang; Zeng, Yongmei; Yang, Gang; Zhang, Yanzong; Deng, Shihuai; Zhang, Jing
Highlights: PHP pretreatment easily achieved SSF at 20% solid loading without special mixing. Relatively lower enzyme and yeast input still work well on PHP pretreated solid. SSF was optimized for maximizing ethanol yield and minimizing enzyme, yeast input. Optimized SSF results were solid loading: 15.3%, enzyme: 13.2 mg/g and yeast: 1.0 g/L. Integrating optimal pretreatment & SSF yielded 155 g ethanol from 1 kg wheat straw. Abstract: Phosphoric acid plus hydrogen peroxide (PHP) pretreatment was employed on wheat straw for ethanol conversion by simultaneous saccharification and fermentation (SSF) at high loadings. Results showed solid loading of PHP-pretreated wheat straw can be greatly promoted to 20%. Although more enzyme input improved ethanol conversion significantly, it still can be potentially reduced to 10–20 mg protein/g cellulose. Increasing yeast input also promoted ethanol conversion, however, the responses were not significant. Response surface method was employed to optimize SSF conditions with the strategy of maximizing ethanol conversion and concentration and minimizing enzyme and yeast input. Results indicated that ethanol conversion of 88.2% and concentration of 69.9 g/L were obtained after 120 h SSF at solid loading of 15.3%, and CTec2 enzyme and yeast were in lower input of 13.2 mg protein/g cellulose and 1.0 g/L, respectively. Consequently, 15.5 g ethanol was harvested from 100 g wheat straw in the optimal conditions.